Kontribusi Kitab Al-Mu’jam Al-Mufahras Karya Arent Jan Wensinck Terhadap Ilmu Takhrijul Hadis - Arifah, Afro' Anzali Nurizzati; Muhid, Muhid; Nurita, Andris (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
Hadith is indeed the main source of teachings upheld by Muslims. Its existence has existed since the time of the Prophet Saw and supported the development of Islam, until finally all criticisms of the hadith of the Prophet Saw appeared after the death of the Prophet Saw. Orientalists have always been judged badly by many hadith scholars because they judge hadith only with one side, but in fact there are several orientalists who contribute to the process of developing hadith, namely the science of takhrij hadith. The development of takhrijul hadith itself developed rapidly among scholars. It's just that the initial support in this takhrij process uses one of the books of orientalist work to date. This article aims to explain orientalist views on hadith along with academic honesty and study of the book of takhrij by orientalists. This research uses a descriptive method with a qualitative approach. The result of this study is that the role of orientalists in the development of hadith and the science of takhrijul hadith is true. In fact, it is very useful for the study of subsequent hadith, in this study also saw his academic honesty in writing works about Islam, especially hadith.